Actionable Metabolic Pathways in Heart Failure and Cancer—Lessons From Cancer Cell Metabolism - Karlstaedt, Anja; Schiffer, Walter; Taegtmeyer, Heinrich (Frontiers in Cardiovascular Medicine, 2018)
Recent advances in cancer cell metabolism provide unprecedented opportunities for a new understanding of heart metabolism and may offer new approaches for the treatment of heart failure. Key questions driving the cancer field to understand how tumor cells reprogram metabolism and to benefit tumorigenesis are also applicable to the heart. Recent experimental and conceptual advances in cancer cell metabolism provide the cardiovascular field with the unique opportunity to target metabolism. This review compares cancer cell metabolism and cardiac metabolism with an emphasis on strategies of cellular adaptation, and how to exploit metabolic changes for therapeutic benefit.